The Chemopreventive Effect of the Dietary Compound Kaempferol on the MCF-7 Human Breast Cancer Cell Line Is Dependent on Inhibition of Glucose Cellular Uptake. - Azevedo, Cláudia; Correia-Branco, Ana; Araújo, João R.; Guimarães, João T.; Keating, Elisa; Martel, Fátima (Nutrition & Cancer, 2015)
Our aim was to investigate the effect of several dietary polyphenols on glucose uptake by breast cancer cells. Uptake of3H-deoxy-D-glucose (3H-DG) by MCF-7 cells was time-dependent, saturable, and inhibited by cytochalasin B plus phloridzin. In the short-term (26 min), myricetin, chrysin, genistein, resveratrol, kaempferol, and xanthohumol (10–100 µM) inhibited3H-DG uptake. Kaempferol was found to be the most potent inhibitor of3H-DG uptake [IC50of 4 µM (1.6–9.8)], behaving as a mixed-type inhibitor. In the long-term (24 h), kaempferol (30 µM) was also able to inhibit3H-DG uptake, associated with a 40% decrease in GLUT1 mRNA levels. Interestingly enough, kaempferol (100 µM) revealed antiproliferative (sulforhodamine B and3H-thymidine incorporation assays) and cytotoxic (extracellular lactate dehydrogenase activity determination) properties, which were mimicked by low extracellular (1 mM) glucose conditions and reversed by high extracellular (20 mM) glucose conditions. Finally, exposure of cells to kaempferol (30 µM) induced an increase in extracellular lactate levels over time (to 731 ± 32% of control after a 24 h exposure), due to inhibition of MCT1-mediated lactate cellular uptake. In conclusion, kaempferol potently inhibits glucose uptake by MCF-7 cells, apparently by decreasing GLUT1-mediated glucose uptake. The antiproliferative and cytotoxic effect of kaempferol in these cells appears to be dependent on this effect.